2017
DOI: 10.1186/s13075-017-1399-5
|View full text |Cite|
|
Sign up to set email alerts
|

The association between sonographic enthesitis and radiographic damage in psoriatic arthritis

Abstract: BackgroundTo examine the association between sonographic enthesitis and the severity of radiographic features of damage in the peripheral and axial joints in psoriatic arthritis (PsA).MethodsA cross-sectional analysis was conducted in patients with PsA. The MAdrid Sonography Enthesitis Index (MASEI) scoring system was used to quantify the extent of sonographic entheseal abnormalities. Radiographic damage in the peripheral joints and spine was assessed by the modified Steinbrocker score (mSS), Modified New York… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 44 publications
0
33
0
3
Order By: Relevance
“…This leads to underappreciation of the early phases of the disease and a concomitant suboptimal treatment during the timeframe of active inflammation, whereas current therapies could potentially alter the natural history of this process. Indeed, several groups have stressed the role of the entheses as an initiating site of inflammation in a proportion of PsA patients who go on to develop synovitis and destructive arthritis (23,(40)(41)(42). However, very little is known about the biology and molecular mechanisms by which proinflammatory resident cells can drive downstream systemic effects.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to underappreciation of the early phases of the disease and a concomitant suboptimal treatment during the timeframe of active inflammation, whereas current therapies could potentially alter the natural history of this process. Indeed, several groups have stressed the role of the entheses as an initiating site of inflammation in a proportion of PsA patients who go on to develop synovitis and destructive arthritis (23,(40)(41)(42). However, very little is known about the biology and molecular mechanisms by which proinflammatory resident cells can drive downstream systemic effects.…”
Section: Discussionmentioning
confidence: 99%
“…They proposed that while the initial trigger of enthesitis may be mechanical microtrauma which can occur in HLA-B*27-negative individuals, in HLA-B*27-positive subjects the inflammatory response is perpetuated and becomes chronic, involving the bone and the adjacent fibrocartilage (33). Consistent with this hypothesis, a recent crosssectional study demonstrated that enthesitis is a marker for worse outcome in patients with PsA, by showing an association between sonographic enthesitis and the extent of peripheral and axial radiographic damage (34).…”
Section: Discussionmentioning
confidence: 85%
“…Weiterführend ist die PsA durch eine Enthesitis gekennzeichnet. Diese kann im Röntgen nicht sicher erfasst werden, wobei das Auftreten der Enthesitis mit dem radiologischen Schweregrad der PsA korreliert [25]. Zur Beurteilung der knöchernen Veränderungen einer PsA im Bereich der kleinen Vorfuß-und Handgelenke wird ebenfalls standardmäßig das Röntgen eingesetzt [26].…”
Section: Psoriasisarthritisunclassified